Manipulation of heteronuclear spin dynamics with microwave and vector light shift - Li, Lintao; Zhu, Bing; Lu, Bo; Zhang, Shizhong; Wang, Dajun (Physical review, 2020)
We report the observation and manipulation of heteronuclear spin dynamics in a spin-1 mixture of ultracold 87Rb and 23Na atoms. The dynamics is driven by the interspecies spin-dependent interaction and shows a pronounced dependence on magnetic fields with influences from both linear and quadratic Zeeman shifts. Similar to the well-studied homonuclear cases, the interspecies spin dynamics can be controlled by tuning the quadratic Zeeman shift with far-detuned microwave fields. In addition, we successfully realize spin dynamics' control with vector light shifts which act as a species-selective effective magnetic field on 87Rb atoms. Both methods show negligible loss of atoms thus will be powerful techniques for investigating spin dynamics with fast temporal and high spatial resolutions.